Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1158/1055-9965.epi-06-0143
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Behavioral Risk Factors for Colorectal Cancer and Colorectal Cancer Screening Status

Abstract: Background: Individuals who are not adherent to colorectal cancer screening have a greater prevalence of several other behavioral risk factors for colorectal cancer than adherent individuals. However, previous relevant studies have typically not considered the co-occurrence of such behavioral risk factors at the individual level. In the current study, we examined the prevalence, patterns, and predictors of multiple behavioral risk factors for colorectal cancer according to colorectal cancer screening status (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 61 publications
3
33
0
1
Order By: Relevance
“…Smokers declared almost twice as low readiness for screening, which may have its roots in their lifestyle associated with a more nihilistic attitude toward health. Similar conclusions were drawn by American authors, who found that smokers and alcohol abusers are less eager to participate in screening [34,35]. These observations lead to the conclusion that a great er emphasis should be placed on the need to screen men, obese persons, smokers and alcohol abusers.…”
supporting
confidence: 78%
“…Smokers declared almost twice as low readiness for screening, which may have its roots in their lifestyle associated with a more nihilistic attitude toward health. Similar conclusions were drawn by American authors, who found that smokers and alcohol abusers are less eager to participate in screening [34,35]. These observations lead to the conclusion that a great er emphasis should be placed on the need to screen men, obese persons, smokers and alcohol abusers.…”
supporting
confidence: 78%
“…Other national studies similarly reported that only between 25 and 42 % of adults with diabetes met physical activity recommendations [16,33,34], that over 16 % of adults with diabetes smoked [35], and that the vast majority were overweight or obese [33]. [21,[36][37][38]. In our study, those with these risk behaviors were no less likely to be up-to-date with CRC screening overall.…”
Section: Discussionmentioning
confidence: 41%
“…Our analysis also indicated that overweight or obese adults with diabetes were more likely to be up-to-date with CRC screening than those who were not overweight or obese. In previous literature, mixed findings have been reported on the association between CRC screening and BMI in the general population [36,41]. Some studies have reported that the relationship between CRC screening and BMI is modified by race or sex [42,43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations